2023
DOI: 10.3390/w15030420
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Indicators for Paleolimnological Studies of the Anthropogenic Influence on the Environment of the Russian Federation: A Review

Abstract: Lake sediments are a reliable source of information about the past, including data of the origin of water bodies and their changes. Russia has more than 2 million lakes, so paleolimnological studies are relevant here. This review deals with the most significant studies of sequential accumulation of pollutants, including heavy metals in recent lake sediments in Russia. The key areas are northwestern regions of Russia (Murmansk Region, the Republic of Karelia, Arkhangelsk Region), the Urals (Chelyabinsk Region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…In the case of Lake Okunozero, this may be due to the activity of trains, cars and land development around the village. The closest large industrial and urbanized area to Lake Okunozero is the city of Petrozavodsk, where earlier studies of small lakes and rivers showed a significant level of heavy metal pollution [10]. On the other hand, the concentrations of Mn decreased in the lower layers and there was no dynamics of the distribution of Mo concentrations.…”
Section: General Description Of Sediment Geochemistrymentioning
confidence: 90%
See 2 more Smart Citations
“…In the case of Lake Okunozero, this may be due to the activity of trains, cars and land development around the village. The closest large industrial and urbanized area to Lake Okunozero is the city of Petrozavodsk, where earlier studies of small lakes and rivers showed a significant level of heavy metal pollution [10]. On the other hand, the concentrations of Mn decreased in the lower layers and there was no dynamics of the distribution of Mo concentrations.…”
Section: General Description Of Sediment Geochemistrymentioning
confidence: 90%
“…The total concentrations of the majority of heavy metals also varied in the studied sapropel core (Figure 3). For example, the total concentrations of Zn, Pb, Cr, Cu, Ni, Co, and Cd rose from the lower to upper layers, which is related to the anthropogenic influence on the lake, as these metals are indicators of the modern environmental transformations [10,[23][24][25]. Herewith, it can be associated both with the local anthropogenic sources, such as emissions from cars and trains, and with the long-range transport of heavy metals [26].…”
Section: General Description Of Sediment Geochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In this wide "Water Environment Pollution and Control" framework, this Special Issue aimed to provide important knowledge and lay a sound scientific foundation for the control and management of water environment pollution by studying the environmental behaviors and bioavailabilities of various pollutants. The thirteen articles in this Special Issue focusing on water environmental pollution and control are mainly divided into four categories: (1) the composition characteristics and environmental behaviors of the pollutants in the surface water (i.e., the Chinese lakes Ulansuhai [1], Hulun Lake [2], Tai Lake [3], Shahu Lake [4], and Russian Ancient lakes [5]); (2) the assessment of groundwater and aquifer interaction [6] and the sources, risks, and management of groundwater pollution [7]; (3) the impact of polluted water on human health [8][9][10]; and (4) the removal of pollutants in water [11][12][13].…”
Section: Introduction To the Special Issuementioning
confidence: 99%
“…Since the call for papers was announced in 2022, and after a rigorous peer-review process, thirteen papers have been accepted for publication in the Special Issue [1][2][3][4][5][6][7][8][9][10][11][12][13], which include eleven research papers [1][2][3][4]6,[8][9][10][11][12][13] and two reviews [5,7]. We offer brief highlights of the published papers below.…”
Section: Introduction To the Special Issuementioning
confidence: 99%